Analisis Strategi Pemasaran STP (Segmenting, Targeting, Positioning) pada UMKM Pengrajin Keramik : (Studi Kasus pada UMKM Denis Souvenir Sulastri) - Abdullah As Shoib; Ayu Putriana Dewi; Dynda Prista; Fajar Dio Wahyu; Sudarmiatin Sudarmiatin (Jurnal Bintang Manajemen, 2024)
The research aims to analyze the application of the STP (Segmenting, Targeting, Positioning) marketing strategy to the MSME ceramic craftsman Denis Souvenir Sulastri in Dinoyo Ceramic Village, Malang. The STP approach is expected to help ceramic craftsmen identify potential market segments, determine the right target market, and strengthen product positions in a competitive market. The method used in this research is descriptive qualitative with data collection through observation and interviews with owners and craftsmen. The research results show that implementing the STP strategy is able to increase the attractiveness of Dinoyo ceramic products among tourists and local consumers who appreciate cultural and aesthetic values. However, the results also show that the implementation of digital marketing strategies still needs to be improved to reach a wider audience range. By understanding market needs and strengthening product positions, this ceramic craft MSME has the potential to become a sustainable local cultural and economic icon in Malang City.